Becoming socially responsible: the implementation of project-oriented problem-based learning - Alwi, Azlin; Hussin, Ruhaya (International Journal of Contemporary Educational Research (IJCER), 2018)
Project-oriented problem-based learning (POPBL) is an alternative approach to innovative teaching and is widely implemented in the classroom. However, little information is gathered pertaining to its implementation in psychology-related subjects. The present study is guided by two objectives: 1) to examine students’ perception of this type of approach, and (2) to determine whether students’ perception improves after the implementation of POPBL. 103 participants aged between 18-24 years old (M = 21.91, SD = 2.14) participated in this study. A measure, named the Students’ Learning Experience Scale (SLES) was constructed to determine participants’ perception of their learning in five aspects: (1) acquired knowledge, (2) soft skills, (3) contribution and engagement, (4) sustainability; and (5) assessments. The results from the present study suggested that the POPBL was indeed highly acceptable and favored by all students. A paired t-test was also conducted to evaluate the effectiveness of the approach on students’ scores on the SLES. The results show that there was a significant difference in the scores for students’ perception of the course before (M = 4.15, SD = .45) and after (M = 4.41, SD = .40); t(87) = (-4.05). p = .000. These findings were further discussed with respect to the current literature on teaching and learning approaches, and the significant implications in developing effective pedagogic strategies.